An investigation into the practices of academics in Departments of Accounting at South African universities : the pressures on educators of professionals to meet the requirements of their profession and those of an academic institution simultaneously - Lubbe, Ilse (School of Education, 2015)
Includes bibliographical references (leaves 83-93).